The First Description of Acidic Blood-Induced Kidney Injury Following Subarachnoid Hemorrhage: The First Experimental Study - Binali Fırıncı; Mehmet Dumlu Aydın (Journal of Behçet Uz Children's Hospital)
Objective: One of the complications of subarachnoid hemorrhage (SAH) is the acidity of blood and cerebrospinal fluid if carotid body/glossopharyngeal-nerve chemoreceptor networks are disrupted. This study aimed to investigate whether the renal arteries and glomeruli are affected by acidic blood pH following SAH. Method: Twenty-six hybrid rabbits were selected of which 5 were used to analyze interactions between carotid bodies and kidneys, 5 were allocated as the sham group that received injections of 1 cc saline, and 16 of them constituted the SAH group in which 1 cc of autologous arterial blood was injected into the cisterna magna. Deaily pH and blood pressure values of all animals were measured before, during, and after surgery for 2 weeks, and then all animals were decapitated. Carotid bodies and atrophic glomeruli of all animals were determined histopathologically. Only pH values, and number of atrophic glomeruli per mm3 (n/mm3) were analyzed statistically. Results: In the study group severe degeneration of perirenal vagal ganglia, renal artery vasospasm, intrarenal hemorrhage, and renal glomerular degeneration were observed. The mean density of atrophic glomeruli in control, sham, and study groups were estimated as 13±37/mm3, 24±5/mm3, and 67±11/mm3, respectively which differed statistically significantly between control, and sham (p<0.005), sham and study (p<0.0005), control and study (p<0.00001) groups. Conclusion: The study showed that acidic blood results in degeneration of the epithelial cells and causes severe vasospasm in renal arteries and glomerular atrophy following SAH, which has not previously been described.